Analysis of Impact of Distributed Photovoltaic on Main Transformer Gap Protection. Issue 1 (1st February 2022) - Tian, G; Yan, P; Hu, X K; Luo, P; Su, C; Zhang, Q
Abstract: Distributed photovoltaic is one of the important energy supplies in new-type power system. Notably, when the main transformer is operated in non-directly grounded mode and distributed photovoltaic is connected to the low-voltage side, faults such as single-phase grounding short-circuit may cause overvoltage problems at the neutral point of the transformer, thereby posing a threat to the insulation at the neutral point. For the main transformer neutral point voltage offset and gap protection problems, this paper first analyzes the fault characteristics of the network, the operation of the line protection and the neutral point voltage offset after the fault occurs. Furthermore, combined with the distributed photovoltaic output characteristics after the near-system protection action, this paper analyzes that the distributed photovoltaic access after the line protection action may cause the neutral point over-voltage offset to deteriorate further. Moreover, under different matching degrees of distributed capacity and local load, the degree of neutral point voltage deviation when a single-phase fault occurs in a substation with distributed photovoltaic is derived. On this basis, the criterion of gap breakdown of the main transformer and relevant suggestions for installing gap protection are given. Finally, based on the simulation analysis of the single-phase ground fault of the grid-connected line, the boundary of neutral breakdown at different fault moments are obtained, thereby effectively guiding distributed photovoltaic to access new-type power system friendly.